STRATEGI PENGEMBANGAN EKOWISATA DI DESA KINARUM KABUPATEN TABALONG - Syarif Hidayat (Lambung Mangkurat University-Indonesia, 2016)
The purpose of this study was to explore the perception of society and tourists to the ecotourism development plan of Kinarum Village, and to formulate the policy plan of ecotourism development of Kinarum Village. The research approach uses a quantitative approach combined with a qualitative approach. Data analysis is done by collecting and arranging data into tabulation form. The results of the analysis and then made interpretation descriptively qualitative in accordance with the objectives of the study. The ecotourism development plan was done through SWOT analysis method. The perception of the village community was very supportive in the development of ecotourism with the hope that the community was involved in the management so that it can increase business opportunities and increase revenue. In addition, the community at the same time can preserve local art and culture and reduce the destruction of forest areas. Perception of visitors to the tourist attraction is very supportive in the development effort Riam Kinarum especially improvements supporting infrastructure such as suspension bridge and hygiene facilities. Recommendation of ecotourism development strategy, that was: (1) complete infrastructure supporting nature tourism activity, especially ecotourism, such as road, bridge, hygiene facility, and others. (2) conduct intensive promotion (3) create policies that are specialized in ecotourism development. (4) ecotourism package development such as bamboo rafting, kayaking, white water rafting, introduction of flora and fauna species, (5) synergizing ecotourism with traditional arts and culture of Dayak Deah, and (6) empowering local people in ecotourism activities.Tujuan penelitian ini adalah menggali persepsi masyarakat dan wisatawan terhadap rencana pengembangan ekowisata Desa Kinarum, dan merumuskan rencana kebijakan pengembangan ekowisata Desa Kinarum. Pendekatan penelitian menggunakan pendekatan kuantitatif yang dikombinasikan dengan pendekatan kualitatif. Analisis data dilakukan dengan cara mengumpulkan dan menyusun data ke dalam bentuk tabulasi. Hasil analisis kemudian dibuat interpretasinya secara deskriptif kualitatif sesuai dengan tujuan penelitian. Rencana pengembangan ekowisata dilakukan melalui metode analisis SWOT. Persepsi masyarakat desa sangat mendukung dalam pengembangan ekowisata dengan harapan agar masyarakat dilibatkan dalam pengelolaannya sehingga dapat menambah peluang usaha dan meningkatan pendapatan. Selain itu masyarakat sekaligus dapat melestarikan kesenian dan budaya lokal serta mengurangi pengrusakan kawasan hutan. Persepsi pengunjung terhadap objek wisata sangat mendukung dalam upaya pengembangan Riam Kinarum terutama perbaikan sarana prasarana penunjang seperti jembatan gantung dan sarana kebersihan. Rekomendasi strategi pengembangan ekowisata, yaitu : (1) melengkapi infrastruktur pendukung kegiatan wisata alam, khususnya ekowisata, seperti : jalan, jembatan, sarana kebersihan, dan lain-lain. (2) melakukan promosi yang intensif (3) membuat kebijakan yang khusus dalam pengembangan ekowisata. (4) pengembangan paket ekowisata seperti : bamboo rafting, kayak, arung jeram, pengenalan jenis flora dan fauna, (5) mensinergikan ekowisata dengan kesenian dan budaya tradisional dayak Deah, dan (6) memberdayakan masyarakat lokal dalam kegiatan ekowisata.